2010
DOI: 10.1123/jsm.24.4.416
|View full text |Cite
|
Sign up to set email alerts
|

How Confident Are You to Win Your Fantasy League: Exploring the Antecedents and Consequences of Winning Expectancy

Abstract: The purpose of this study is to propose a conceptual model for investigating the antecedents and consequences of winning expectancy in the fantasy sport consumption context. Employing the illusion of control theory as a conceptual framework, the study hypothesized that perceived football knowledge, perceived ease of use the service Website, and enjoyment as predictors of winning expectancy and time and money involvement as consequences. The proposed model is tested using a convenience sample (N = 244) of colle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 28 publications
1
15
0
Order By: Relevance
“…Their study found that four (achievement, ownership, bragging rights, and socialization) of the six motives predicted involvement with fantasy sports and that three (achievement, socialization, and amusement) of the six motives affected information-seeking behavior. In addition, Kwak, Lim, Lee, and Mahan (2010) revealed that sport knowledge and hedonic experience are positively correlated with spending. Based on the findings identified by these studies, the involvement, information-seeking, and spending were chosen to test validity of the FanSMI.…”
Section: Measurementmentioning
confidence: 94%
“…Their study found that four (achievement, ownership, bragging rights, and socialization) of the six motives predicted involvement with fantasy sports and that three (achievement, socialization, and amusement) of the six motives affected information-seeking behavior. In addition, Kwak, Lim, Lee, and Mahan (2010) revealed that sport knowledge and hedonic experience are positively correlated with spending. Based on the findings identified by these studies, the involvement, information-seeking, and spending were chosen to test validity of the FanSMI.…”
Section: Measurementmentioning
confidence: 94%
“…The participants' level of knowledge, familiarity, involvement in the games and agreeably so, the probability of winning the fantasy games are largely determined by chance (Kwak, Lim, Lee & Mahan, 2010). It is within the same vein that some scholars such as Bernhard and Eade (2005) and Davis and Duncan (2006) have rated fantasy sport on a similar pedestal as gambling or the two as 'a flip side of a coin.'…”
Section: H1: Perceived Eustress (Peu) Is Positively Related To Attitumentioning
confidence: 99%
“…As stated earlier, the parameters included in our model are by no means exhaustive of the motivations for out-of-market viewership. For instance, fantasy football participation is immensely popular (Nesbit & King, 2010) and sport management scholars have documented the strong relationship between game viewership and fantasy league participation (Drayer, Shapiro, Dwyer, Morse, & White, 2010;Kwak, Lim, Lee, & Mahan, 2010;Suh, Lim, Kwak, & Pedersen, 2010). Thus, although fantasy team considerations were not a relevant inclusion in our model given the purpose of this study, they are certainly an excellent area for future exploration.…”
Section: Discussionmentioning
confidence: 98%